2018
DOI: 10.1093/dnares/dsy033
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming challenges in variant calling: exploring sequence diversity in candidate genes for plant development in perennial ryegrass (Lolium perenne)

Abstract: Revealing DNA sequence variation within the Lolium perenne genepool is important for genetic analysis and development of breeding applications. We reviewed current literature on plant development to select candidate genes in pathways that control agronomic traits, and identified 503 orthologues in L. perenne. Using targeted resequencing, we constructed a comprehensive catalogue of genomic variation for a L. perenne germplasm collection of 736 genotypes derived from current cultivars, breeding material and wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Genotyping was performed at the population level by estimating the allele frequencies of nuclear genome SNP markers through sequencing the pools of 300 bulked DNAs. Two methods were used to sequence a reduced, yet consistent fraction of the genome: 1) Genotyping by Sequencing (GBS) described by Elshire et al (2011) in order to provide genome-wide coverage and 2) highly multiplexed amplicon sequencing (Hi-Plex) developed by Floodlight Genomics LLC (Knoxville, TN, USA, https://floodlightgenomics.com ) to target candidate genes putatively involved in aerial morphogenesis ( Veeckman et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotyping was performed at the population level by estimating the allele frequencies of nuclear genome SNP markers through sequencing the pools of 300 bulked DNAs. Two methods were used to sequence a reduced, yet consistent fraction of the genome: 1) Genotyping by Sequencing (GBS) described by Elshire et al (2011) in order to provide genome-wide coverage and 2) highly multiplexed amplicon sequencing (Hi-Plex) developed by Floodlight Genomics LLC (Knoxville, TN, USA, https://floodlightgenomics.com ) to target candidate genes putatively involved in aerial morphogenesis ( Veeckman et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…For the Hi-Plex sequencing, primers were designed with Primer3 (Untergasser et al 2012) in candidate genes using previous knowledge on their allele sequence polymorphism (Barre et al 2014;Veeckman et al 2019). A set of 185 amplicons of 80-140 bp were sequenced (Table S3).…”
Section: Genotypingmentioning
confidence: 99%
“…We also showed that genetic diversity estimates based on amplicon sequencing of pooled-plant material are similar to those of single-plant material, which further reduces costs per sample. Since PCR is a very robust and versatile method, improvements to the genetic diversity estimates based on multispecies amplicon can be achieved by increasing the number of amplicons analyzed, by varying amplicon sizes, by varying PCR conditions (e.g., multiplex PCR can reduce the processing time needed for each amplicon; Veeckman et al, 2019), or by adapting sequencing approaches (e.g., pool sequencing can be used to characterize larger plant populations).…”
Section: Discussionmentioning
confidence: 99%
“…The plant material used in this study consisted of 580 genotypes from diverse origins ( Supplementary Table 1 ) chosen to represent a large genetic and phenotypic diversity ( Veeckman et al, 2018 ). Among them, 42% were chosen among breeding material from ILVO, DSV, and Barenbrug, 22% represented commercial cultivars and 36% originated from wild accessions (of which 76% were of French origin).…”
Section: Methodsmentioning
confidence: 99%
“…The genetic markers reported in Veeckman et al (2018) were used. These markers describe the sequence diversity in 503 candidate genes involved in plant development, plant architecture, phytohormone biosynthesis, and response pathways, and cell wall composition.…”
Section: Methodsmentioning
confidence: 99%